Mode identification for reliability improvement of MMC. (November 2020) - Fan, X.F.; Qiu, D.Y.; Zhang, B.; Chen, Y.F.; Huang, R.H.; Cao, W.Y.; Xu, S.K.; Fu, C.; Rao, H.; Li, L.C.
Abstract: In order to improve the reliability of Modular Multilevel Converters (MMC), the unexpected modes which will lead to unintended outcomes should be identified. In this paper, the unexpected modes of semi-full-bridge (SFB) submodule are detected through superposition of passive components on different switching states according to the operation principles. Then, further analysis on triggered conditions and effect of unexpected modes is helpful to avoid potential threat on MMC, which is also an effective way to protect the normal operation of MMC.